Implementasi Link and Match antara SMK dan Dunia Industri guna Mempersiapkan Lulusan Siap Kerja di Purwokerto - novelia, mutiara; Hanif, Muh. (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to analyze the implementation of the link and match program between SMK TI Bina Citra Informatika Purwokerto and the business and industrial sector (DUDI) in improving graduates' work readiness. The study is motivated by the persistent gap between vocational graduates' competencies and industry requirements, as reflected in the low employment absorption rate despite the implementation of various industry partnership programs. Design/methods – This study employed a qualitative approach using a case study design. Data were collected through observations, semi-structured interviews with the Vice Principal for Curriculum and students, and document analysis, including Memoranda of Understanding (MoUs), industry partnership records, tracer study reports of the 2024/2025 graduates, and documents related to the Special Employment Exchange (BKK). Data were analyzed using an interactive qualitative analysis model consisting of data reduction, data display, and conclusion drawing. Data credibility was ensured through source triangulation. Findings – The findings indicate that the link and match program has been implemented through curriculum synchronization, one-semester Field Work Practice (PKL), guest lecturer programs, teacher internships, and graduate recruitment in collaboration with three industrial partners. However, these collaborative initiatives have not yet resulted in optimal graduate employment outcomes. Of the 67 graduates, only 20.9% were employed, while 65.7% remained in the job-seeking phase. Limited mastery of basic vocational competencies and employability skills was identified as the primary factor constraining graduates' work readiness. These findings suggest that the effectiveness of the link and match program depends not only on sustained collaboration between vocational schools and industry, but also on strengthening competency-based learning and expanding industrial partnership networks